Tipikal Kuantitas Infiltrasi Menurut Karakteristik Lahan (Kajian Empirik di DAS Cimanuk Bagian Hulu) - Dede Rohmat (Forum Geografi, 2009)
Rate of infiltrate can be conduct as function of permeability, suction head and moisture of soil parameter. The parameters have close relationship with soil physical characteristics. That relation can be formulated by empirical research. This study have aim to get typical infiltrate quantity based on land characteristics. Method of Green-Ampt infiltrate developed and used to study typically of infiltrate capacity on Upstream of Watershed (Case on Upstream Cimanuk Watershed). Research conducted use empirical and analytical approach.Study conducted at Oxisol Soil occupied by five kinds of land use. There are 96 soil samples was gathered, taken away from 16 observation points. About 12 parameters of soil physical properties were analyzed to each soil sample. The study covering, development of typical capacities infiltrate pursuant on empiric data at multifarious land characteristics (forest; agro forestry; second crops (palawija); settlement; and non-arable land). The precipitation intensity has been formulated as function of rainy duration and its probabilities. K formulated as function of volumetric water content; rapid drainage pores, and slow drainage pores (K = f (θ, ηc, ηl). Parameter of y, formulated as function of soil moisture (ψ = f (θ)). Parameter of F (T) dummy, formulated as function of p and t; (F (T) Dummy=F (t,p)). So that pursuant to empirical data, rate of infiltrate f (t)) of Green Ampt developed as f (t = f (θ, ηc, ηl, τ, π); and infiltrate cumulative can be calculated by F (F = f (t), t). Infiltrate of every kinds of land characteristics have pattern which much the same to, but differ in its quantity.